2018
DOI: 10.4103/aer.aer_96_18
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of relationship between Vitamin D deficiency and pain severity in patients with low back pain: A retrospective, observational study

Abstract: Background:Vitamin D is associated with musculoskeletal function in our body, and its deficiency is a common health problem all over the world. Low back pain (LBP) is an important health problem in terms of low quality of life, loss of work power, and cost of diagnosis and treatment approaches.Aims:The purpose of this study is to investigate the relationship between pain severity and Vitamin D deficiency in patients who applied to pain polyclinic with LBP.Settings and Design:This was a retrospective, observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
1
15
2
Order By: Relevance
“…Lower serum concentrations of 25 hydroxyvitamin D were associated with higher scores of LBP in VAS. In favor of findings in the current study, in a retrospective observational study in Turkey by Gokcek et al [26] there was an inverse correlation between concentration of 25 hydroxyvitamin D and VAS score in patients with LBP ( r = − 0.594, p < 0.001). In contrast, in a nested case–control study by Heuch et al [8], no association was found between 25 hydroxyvitamin D status and risk of chronic LBP (OR per 10 nmol/l 25(OH)D = 1.01, 95% CI 0.97 to 1.06).…”
Section: Discussioncontrasting
confidence: 88%
“…Lower serum concentrations of 25 hydroxyvitamin D were associated with higher scores of LBP in VAS. In favor of findings in the current study, in a retrospective observational study in Turkey by Gokcek et al [26] there was an inverse correlation between concentration of 25 hydroxyvitamin D and VAS score in patients with LBP ( r = − 0.594, p < 0.001). In contrast, in a nested case–control study by Heuch et al [8], no association was found between 25 hydroxyvitamin D status and risk of chronic LBP (OR per 10 nmol/l 25(OH)D = 1.01, 95% CI 0.97 to 1.06).…”
Section: Discussioncontrasting
confidence: 88%
“…Finally, it is necessary to mention the limitations of the study. Due to the social distancing requirements, reduced mobility, and meeting restrictions, it was not possible to include certain measurements, such as inflammatory biomarkers and vitamin D levels, which could have provided relevant information regarding LBP risk factors, as observed in previous studies [ 42 , 43 , 44 , 45 ]. Furthermore, the LBP intensity was ascertained four weeks after the order of confinement.…”
Section: Discussionmentioning
confidence: 99%
“…Gokcek et.al. (26) there was an inverse correlation between concentration of 25 hydroxyvitamin D and VAS score in patients with LBP (r = -0.594, P < 0.001). In contrast, in a nested case-control study by Heuch et.al (8), no association was found between 25 hydroxyvitamin D status and risk of chronic LBP (OR per 10 nmol/L 25(OH)D=1.01, 95% CI 0.97 to 1.06).…”
Section: Discussionmentioning
confidence: 93%